Judaism before Jesus : the ideas and events that shaped the New Testament world - Tomasino, Anthony J., 1961- (InterVarsity Press, 2003)
Persian impact on Judaism - Greeks in the East - Jewish diversity in the Hasmonean era - Hellenistic inheritance - Romans and the Jews - Messianic hopes.